Integrated Health Resource Management Model for Public Health Emergency of COVID-19 Pandemic Using Advanced Execution Premium and Government Big Data Analytics of Thailand - คำหา เชาวรินทร์ (Journal of Health Science of Thailand, 2024)
The objective of this study was to develop integrated health resource management model for COVID-19 using advanced execution premium and government data service in Thailand. It was a mixed method research which consisted of 3 phases: (1) draft prototype; (2) develop prototype; and (3) test prototype. The samples of this study included 100 representatives from tertiary hospitals, 20 administrators, and 11 public health specialists. The sample were conducted via questionnaire and group discussion guidelines that established and developed by content analysis and reliability. Quantitative data were analyzed by descriptive statistics and inferential statistics which included confirmatory factor analysis, structural equation modeling, and qualitative data were analyzed through content analysis. Results of this research found that health resource management model for public health emergency consisted of 10 components: (1) situation analysis; (2) integration; (3) management structure; (4) strategy; (5) leadership and management; (6) health manpower; (7) health information; (8) health finance; (9) health service system; and (10) health resource. The structural equation modeling analysis has shown that the causal factor relation of health resource management model for public health emergency was consistent with empirical data at very good level (P–value = 0.0994, Chi-square = 6.265, TLI = 0.987, CFI = 0.997, SRMR = 0.015, RMSEA = 0.031, AIC = 10308.042) The results of health resource management model for public health emergency development caused 6 operational guidelines which were (1) guidelines for managing resources (big data); (2) resource estimation guidelines; (3) guidelines for allocating and distributing resources; (4) defining resource utilization recommendations; (5) preparation of policy proposals; and (6) guidelines for data presentation to chief executive. This study revealed that the policy proposals supposed to create participation of resources management in emergencies of government public health, private sector, and people to link operation and resources exchange for all dimensions and personnel potential should be developed through both short-term and long-term resource management courses to be able to administer the management system. Moreover, research and development should be undertaken to produce the essential public health resources in the country for supporting shortage situations.